2018
DOI: 10.1111/josh.12690
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Active Commuting to School, Adiposity, Fitness, and Cognition in Spanish Children: The MOVI‐KIDS Study

Abstract: BACKGROUND Walking and bicycling (active commuting) to school may be a useful strategy to increase the daily amount of physical activity, and, potentially, improve children's health. However, it is unclear whether active commuting to school (ACS) has the potential to improve physical health and cognitive performance in children. Our aim was to examine the relationship between ACS with adiposity indicators, physical fitness, and cognitive performance in 4‐ to 7‐year‐old children. METHODS We conducted a cross‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 42 publications
(125 reference statements)
3
40
0
2
Order By: Relevance
“…All of the studies had approximately 50.00% girls as a part of their sample, with the lowest and the highest percentage being 42.47% [44] and 53.26% [42], respectively. Most of the studies (n = 10) were cross-sectional studies [42,[45][46][47][48][49][50][51][52][53], and two were prospective studies [43,44]. Eight studies accounted for socioeconomic status either by asking their socioeconomic status or by using parental education as a proxy for it.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…All of the studies had approximately 50.00% girls as a part of their sample, with the lowest and the highest percentage being 42.47% [44] and 53.26% [42], respectively. Most of the studies (n = 10) were cross-sectional studies [42,[45][46][47][48][49][50][51][52][53], and two were prospective studies [43,44]. Eight studies accounted for socioeconomic status either by asking their socioeconomic status or by using parental education as a proxy for it.…”
Section: Study Selectionmentioning
confidence: 99%
“…All studies measured active commuting in the context of commuting to school; either to, from or both. Seven studies [43,45,[48][49][50][51][52] reported the percentage of their sample that engaged in active commuting, and it ranged from 12.00% to 70.41%.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations